ANALISIS AKTIVITAS BELAJAR SISWA DENGAN INTERVENSI PEMBELAJARAN OPEN INQUIRY BERBANTUAN MEDIA PhET SIMULATIONS - Rahmawati, Treeas Adinda; Martini, Martini; Mahdiannur, Muhamad Arif (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
Hands-on, student-centered experiential learning can foster motivation and interest that can develop students' competencies in accommodating skill development, content comprehension, and assimilation of new knowledge. The purpose of this study is to determine the implementation and learning activities of open inquiry assisted by PhET Simulations media. This study uses an observational research design involving 18 grade VIII students. Data collection is carried out by observation. The results of the study showed that the implementation and learning activities using the open inquiry learning model assisted by PhET Simulations media during the three meetings were carried out at all stages and the results of active instruction observation were more dominant. Students are very enthusiastic during learning activities in conducting experiments to complete assignments, and discussions with their groups. Based on this presentation, it can be concluded that the intervention of the open inquiry learning model assisted by PhET Simulations media in the learning process has a great impact on students. Students become active and directly involved in learning, and emphasize direct experience to students so that they can construct knowledge and have an impact on the training of students' proposing action and interpreting result skills. This learning model can be a good alternative for teachers in teaching in the classroom.